Comparing different thrombectomy techniques in five large-volume centers: a 'real world' observational study. (28th September 2017) - Hesse, Amélie Carolina; Behme, Daniel; Kemmling, André; Zapf, Antonia; Hokamp, Nils Große; Frischmuth, Isabelle; Maier, Ilko; Liman, Jan; Tsogkas, Ioannis; Buhk, Jan-Hendrik; Tran, Julia; Fiehler, Jens; et al.
Abstract : Background and purpose: Thrombectomy has become the standard of care for acute ischaemic stroke due to large vessel occlusion. Aim of this study was to compare the radiological outcomes and time metrics of the various thrombectomy techniques. Methods: In this retrospective, multicenter study we analysed the data of 450 patients with occlusion of the anterior circulation, treated in five high-volume center from 2013 to 2016. The treatment techniques were divided in three categories: first-pass use of a large-bore aspiration-catheter; first-pass use of a stent-retriever; and primary combined approach (PCA) of an aspiration-catheter and stent-retriever. Primary endpoints were successful reperfusion and groin to reperfusion time. Secondary endpoints were the number of attempts and occurrence of emboli in new territory (ENT). The primary analysis was based on the intention to treat groups (ITT). Results: The ITT-analysis showed significantly higher reperfusion rates, with 86% of successful reperfusion in the PCA-group compared with 73% in the aspiration group and 65% in the stent-retriever group. There was no significant difference in groin to reperfusion time regarding the used technique. The secondary analysis showed an impact of the technique on the number of attempts and the occurrence of ENTs. Lowest ENT rates and attempts were reported with the combined approach. Conclusions: The combined first-pass deployment of a stent-retriever and an aspiration-catheter was the most effective technique for reperfusion of anterior circulation large vessel occlusion. Our results correlate with the latest single-centrere studies, reporting very high reperfusion rates with PCA variations.